The role of librarians and information professionals in the prevention and control of HIV/AIDS in Nigeria (2008)
There has been a change, of recent in the nature of work of librarians and information professionals, due to the emergence of deadly diseases like AIDS as well as the change in information needs of the local community. This change requires much more professional expertise, updated knowledge and critical thinking and involvement in the process of developing effective AIDS literary programmes. Librarians and information professionals can provide dedicated services to society by helping to manage and access AIDS information. This study, therefore, highlighted strategies for effective collaboration by librarians and information professionals, in the context of AIDS literary promotion efforts. The study further highlighted the challenges in the process of empowering people as regards campaign against AIDS. Suitable measures for addressing the challenges, to achieve essential success in the campaign against AIDS are also identified.